2021
DOI: 10.1186/s12912-021-00621-3
|View full text |Cite
|
Sign up to set email alerts
|

Mealtime caregiving approaches and behavioral symptoms in persons living with dementia: a longitudinal, observational study

Abstract: Background Behavioral symptoms during mealtime can prohibit persons living with dementia from obtaining sufficient nutrition. However, little research has examined the relationship between behavioral symptoms and caregiving approaches. This study examines this relationship and further explores which specific caregiver behaviors were related to behavioral symptoms among persons living with dementia. Methods A secondary data analysis was performed us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
1
4
1
Order By: Relevance
“…Staff task-centred approaches were not correlated with resident behaviours, inconsistent with previous reports that supported temporal or associative relationships with resident agitation (Gilmore-Bykovskyi et al, 2015;Lee et al, 2021) and aspiration (Gilmore-Bykovskyi & Rogus-Pulia, 2018) during mealtimes, and with resident resistiveness to care during hygienic care (Belzil & Vézina, 2015). The non-significant findings could be related to the dichotomisation of staff task-centred approaches and/ or multivariable analyses that examined associative (vs. temporal) relationships in this study.…”
Section: Staff Task-centred Approachescontrasting
confidence: 99%
See 1 more Smart Citation
“…Staff task-centred approaches were not correlated with resident behaviours, inconsistent with previous reports that supported temporal or associative relationships with resident agitation (Gilmore-Bykovskyi et al, 2015;Lee et al, 2021) and aspiration (Gilmore-Bykovskyi & Rogus-Pulia, 2018) during mealtimes, and with resident resistiveness to care during hygienic care (Belzil & Vézina, 2015). The non-significant findings could be related to the dichotomisation of staff task-centred approaches and/ or multivariable analyses that examined associative (vs. temporal) relationships in this study.…”
Section: Staff Task-centred Approachescontrasting
confidence: 99%
“…Comparatively, task‐centred care prioritises activities without adequate consideration of individual needs and preferences and focuses on completion of activities for (rather than with) the individual. Task‐centred care approaches, including providing full assistance for residents with some eating independence, verbal controlling and inappropriate touch, are correlated with disengagement, behavioural challenges and decreased intake (Lee et al, 2021 ; Morrison‐Koechl et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding negative interaction, however, we found that not all care provider-initiated interactions are positive. This also accords with earlier observations, which showed that there are task-centered care provider behaviors that are related to behavioral symptoms (e.g., agitation) or resistiveness to care among persons living with dementia [ 30 , 31 ]. Fortunately, there is room for improvement in the scope of interaction initiated by care providers through educational or institutional efforts.…”
Section: Discussionsupporting
confidence: 91%
“…Prior research showed that staff task-centered care and lack of interaction were associated with resident agitation, and recommended that, when encountering agitation, staff avoid task-centered care (eg, verbal controlling, inappropriate touch) or no response and instead promote person-centered approaches ( 47 ). Although person-centered care has been highly recommended, our study showed that person-centered care may potentially trigger resistive behaviors.…”
Section: Discussionmentioning
confidence: 99%